O trinômio texto-som-imagem na performance de Elis Regina das canções Black is Beautiful (1970), Onze Fitas (1979), e Essa Mulher (1979). - Deniele Naiara Perotti Mello (2019)
Analysis of the trinomial text-sound-image in the performances of Elis Regina in three songs: Black is Beautiful (1972), recorded for the 1Plus program of the Südwestfunks channel of the German public television network, Onze Fitas (1979), recorded live at the Montreaux Jazz Festival and Essa Mulher (1979), also recorded live for the Elis Regina Carvalho Costa Special, presented by Rede Globo de Televisão. From the tools of the mAAVm method (BORÉM, 2018), represented by the structuring of MaPAs (Audiovisual Performance Maps), EdiPAs (Visual Performance Editions) and Circumplex Models of Affects in Music of each song, we observed the musical eclecticism of Elis Regina, as well as her pioneering approach to progressive themes in sensitive moments of the political and social scene. A close relationship between the text (lyrics) or context, sounds (vocal and instrumental effects) and images (facial expressions, choreographies, costumes, scene objects and lighting) were observed in their performances, merging into an amalgam. The building of climaxes and articulation of the musical form is achieved and emphasized through Segmentation, Synchronization Points, Activation Contours, Kinematics and Dynamics revealing a detailed planning of its Cinesfera on stage and a highly structured performance construction. It was also verified the possibility of using the mAAVm method and its tools as a resource to aid the process of construction of the performance of the popular singing student, since its mechanisms favor the manipulation and analysis of the performances recorded in video.